Development Strategy of Creative Economy-Based Village: A Case Study of Kandri Tourism Village in Semarang Regency - Adhi Susano; Sutrisno Sutrisno; Pudji Astuty (Jurnal Indonesia Sosial Sains, 2022)
The Implementation of e-government in Village Governments can be the main intervention in driving villages towards progress. This type of research is Descriptive Research. The approaches used are qualitative and conceptual approaches. The data source used is secondary data. Data analysis is carried out descriptively and qualitatively. Conclusions are drawn using deductive methods, which means drawing conclusions from general to specific, especially related to the research topic, namely the Development Strategy of Creative Economy-Based Tourism Villages. This research yields findings that the implementation of social media and digitalization in Kandri tourism village has been very effective. Visitors can easily obtain information about the tourism village and directly fill out online reservation forms, complete with available tour packages. Emphasizing the concept of "from the community, for the community," the management of tourism digitalization in Kandri tourism village starts with the planning process, creating social media accounts and a website for promotional purposes. The presence of ideas from the community to introduce something new in their village is considered a success for the community. The community's skills in managing existing natural resources can be considered proficient. The community empowerment process carried out in Kandri Tourism Village is in line with the potential held by the community, taking into account the social, cultural, and economic aspects of the community. Throughout this process, the community has become the actors and determinants of the development and growth of Kandri Tourism Village. Through consultative forums conducted by the village government with the community, opportunities are given for the community to propose development programs and collectively make decisions to build Kandri Tourism Village.